Empowering the West Java Smart Digital Community Information Group (KIM) through a Seminar on Creating Engaging Social Media Content Using Canva - Fikri Emsa Silmi; Enang Rusnandi; Raden Deden Ahmad Hidayat; Yuda Purnama Putra; Endra Abdul Hadi; Ade Taopik Hidayatuloh (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2026)
The rapid development of digital technology has significantly changed the way people communicate, particularly through social media as the primary medium for disseminating information. Community Information Groups (KIM) play a strategic role as local information agents responsible for delivering educational and informative content to the public. However, limited skills in designing engaging social media content remain a major challenge in improving communication effectiveness. This community service activity aims to improve digital literacy and content design skills among KIM Jabar Pinter Digital members through a seminar on the use of Canva. The method used was an interactive seminar with a participatory approach, including lectures, demonstrations, and discussions. The results showed an increase in participants' understanding of visual design principles, the use of Canva, and their ability to create more engaging and communicative social media content. This activity contributed to strengthening digital literacy and improving the quality of information dissemination within the community.